Market valuation of corporate reputation - Arayssi, Mahmoud (2018)
Brand associations affect image and one source of brand association is a company’s reputation. While the relationship between a positive corporate reputation and operational performance is intuitively appealing, there has been relatively little empirical research. This study, using a summary measure from the Fortune survey of America’s most admired companies’, seeks to empirically test the relationship and thereby determine whether firms with a positive brand image, that is those with a positive reputation, experience an economic benefit. Fortune’s summary measure is used as a proxy for intangible assets, such as internally generated goodwill, customer service and intellectual capital. Findings focus around the addition of this summary value to market value in terms of a significant market value premium, superior financial performance, and lower cost of capital. Given these findings, marketing managers would do well to strive to build and maintain a positive reputation.